PO82 | Retrospective application of the TH2 score in a multicenter cohort of ITP patients: a reliable predictive tool or a score in need of refinement? (Bleeding, Thrombosis and Vascular Biology)
Background: Immune thrombocytopenia (ITP) presents a dual risk of bleeding and thrombosis. While TPO receptor agonists (TPOra) effectively restore platelet counts and reduce bleeding, they may not fully prevent thrombosis. CV events, observed even with low platelet levels, suggest inflammation plays a secondary role. SYKi (e.g., fostamatinib, FST) may help by mitigating inflammation. The TH2 score (Balitsky AK et al., Blood 2018 ) was designed to help clinicians balance thrombotic and bleeding risks in treatment decisions. However, its use lacks international consensus, and its effectiveness in preventing CV events through tailored therapy remains uncertain. Aim: Retrospective evaluation of the TH2 score in ITP: its role in CV event prevention and therapy guidance.